(untitled) (Al-Academy, 2024)
This research is based on the study (the knowledge of the environment and its representation in the results of the students of the technical education department) and the research includes four chapters, the first chapter (the problem of the research, its importance, its purpose, its limits, and the terms contained in the title of the research), the second chapter included the theoretical framework and the previous studies, which included the theoretical framework of the discussion about reading awareness and ended with a set of indicators, while the third chapter included the research procedures, which included the research complex, which amounted to (50) of the results of the students of the technical education section of the subject manual work, (3) actions were selected in a deliberate manner, then the research tool, and statistical methods and sample analysis, while the fourth chapter included research results, conclusions, and proposals, and the researcher reached a sentence of conclusions; borrowing neglected materials from the environment to produce artistic works that are characterized by beauty is an indication of the students’ possession of a level of awareness towards their environment.